Enforcement Proceedings During Martial Law In Ukraine: Issues, Prospects, And Borrowing Positive Foreign Practices - Sergiienko, Nataliia; Suslin, Serhii; Pyrohovska, Vira; Snidevych, Oleksandr; Bondar, Iryna (Jurnal Cita Hukum, 2026)
This article examines the current state of legal regulation of enforcement proceedings in Ukraine under the conditions of martial law. The aim of the study is to identify systemic legal and institutional problems that impede the proper functioning of enforcement mechanisms during wartime and to outline directions for their improvement based on the experience of selected foreign jurisdictions. The methodology combines general scientific and special legal methods, including analysis, synthesis, comparative legal analysis, and hermeneutics. The article identifies key challenges such as the suspension of enforcement measures, the limited access of claimants to judicial remedies, and gaps in legislative regulation. The study also reviews the practices of Sweden, Germany, and Poland, highlighting their successful models of ensuring enforcement continuity in crisis conditions. Based on the comparative analysis, proposals are made to modernize Ukrainian legislation in this area. Authors emphasize the importance of balancing state security interests with the protection of creditors’ rights and ensuring legal certainty for all participants in enforcement proceedings. The scientific value of the article lies in the formation of a proposals for improving the legal regulation of enforcement of decisions, taking into account the conditions of martial law, based on the experience of foreign countries, in particular, certain EU member states. The article was prepared as part of the scholarship work of the Verkhovna Rada of Ukraine. The article was prepared as part of the scientific (scientific and technical) work “Enforcement of court decisions, other bodies (officials)” (state registration number: 0125U003345).